Olfactory Neuroblastoma Treated by Endoscopic Surgery Followed by Combined External Beam Radiation and Gamma Knife for Optic Nerve and Chiasm Sparing: A Case Report. (9th November 2011) - Jiang, Hansi Z.; Elaimy, Ameer L.; Jones, Guy C.; Mackay, Alexander R.; Fairbanks, Robert K.; Lamoreaux, Wayne T.; Demakas, John J.; Cooke, Barton S.; Lee, Christopher M.
Abstract : We describe the multimodality treatment regimen of a 53-year-old man diagnosed with olfactory neuroblastoma (Kadish stage C) in the right nasal cavity extending into the ethmoid sinus and across the cribriform plate. Endoscopic surgery for tumor resection was followed by a combination of external beam radiotherapy and stereotactic radiosurgery boost with concurrent chemotherapy. The novel combination of dual radiation therapies allowed for the preservation of the nearby optic structures while providing an adequate dosage to a sufficient volume of the afflicted tissue.